Gamification: An Effective Strategy for Developing Soft Skills and STEM in Students - Nisaul Barokati Seliro Wangi; Muh Barid Nizarudin Wajdi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study aims to investigate the effectiveness of gamification in developing soft skills and STEM (science, technology, engineering, and mathematics) among students. The background of this study is the low interest and achievement of students in STEM fields, as well as the lack of 21st century skills, such as creativity, collaboration, communication, and problem-solving, that are needed in the digital era. This study uses an experimental method with a pretest-posttest control group design. The sample of this study is grade X students from three public high schools in Lamongan, namely SMA Negeri 2 Lamongan, SMAN 1 Sukodadi, And SMA Negeri 1 Babat, who are divided into two groups, namely the experimental group that receives learning with gamification, and the control group that receives regular learning. The instruments of this study are STEM ability tests and soft skill questionnaires compiled based on predetermined indicators. This study produces findings that there are significant differences between the experimental and control groups regarding STEM ability and soft skills. The experimental group shows higher improvement than the control group. This indicates that gamification can be an effective strategy for developing soft skills and STEM among students. This study contributes to developing the theory and practice of gamification in education, especially in STEM fields. This study also provides suggestions for teachers, schools, and future researchers.